EXPLORING FIRM VALUE THROUGH VALUE INVESTING: EVIDENCE FROM LARGE-CAP COMPANIES ON THE INDONESIA STOCK EXCHANGE - Taufik Hidayat B. Tahawa; Eni Novitasari; Hisyam Ichsan (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This research investigates the relationship between the Price-to-Earnings Ratio (P/E), Debt-to-Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), and the Price-to-Book Value (PBV) of large-cap companies listed on the Indonesia Stock Exchange (IDX) in 2026. The study adopts a quantitative research design and utilizes secondary data obtained through purposive sampling. Multiple linear regression analysis was performed using IBM SPSS Statistics to evaluate the proposed relationships. The empirical evidence demonstrates that P/E, DER, ROA, and ROE each have a positive and significant influence on PBV, both individually and simultaneously. The regression model explains 48.1% of the variation in PBV (R² = 0.481), while the remaining 51.9% is associated with variables not included in this research. Overall, the findings indicate that valuation measures, capital structure, and profitability are important drivers of firm value and may serve as useful considerations for investors implementing value investing strategies.